If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + 4) + -3 = 3 Reorder the terms: 5(4 + 2x) + -3 = 3 (4 * 5 + 2x * 5) + -3 = 3 (20 + 10x) + -3 = 3 Reorder the terms: 20 + -3 + 10x = 3 Combine like terms: 20 + -3 = 17 17 + 10x = 3 Solving 17 + 10x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + 10x = 3 + -17 Combine like terms: 17 + -17 = 0 0 + 10x = 3 + -17 10x = 3 + -17 Combine like terms: 3 + -17 = -14 10x = -14 Divide each side by '10'. x = -1.4 Simplifying x = -1.4
| 49x-20x-10=0 | | (3x-4)+2=1 | | 2x=-6+-12 | | 2(x+4+3)=6 | | 6+-12=6 | | -5m+6=-8m+3(-8-4m) | | 6(1+5y)=(m-2) | | -3(x-3)+3=6 | | 6x-10+3x=0 | | -8(-x-6)+10=-2 | | 1208-41x=14x+53 | | -8(-x-6)+10=2 | | 5h(t)=7t-t^2 | | 12y-2=13y+4 | | 9x^2+x-22=0 | | 6-4=6x-8x+8 | | 3(2x-3)+2=3 | | 10x-9=2-5x | | 4x-2=13y+4 | | 7x-13-4x=7x-6 | | x^2-12x+228=0 | | 6x(3x+10)=14 | | 2x+2(x-6)=8x-6(x-10) | | 13xy+14y^2=0 | | 4x+4=-23+x | | lg(3x+4)=2 | | -1+5x=-7x+83 | | -6(1-4a)=66 | | 5x+4=-24+x | | x^6+8x^3-6=0 | | 4x*2+10x+10x+25= | | 0.5h+3=0.7h-3 |